Effect of turbo A/R ratio on a high speed turbocharged automotive diesel engine. (2018) - Kumar, K. Senthil; Amarnadh, T. Gandhi; Gupta, Akshay
In light of the recent trend to improve fuel economy and emission control in diesel engines to meet future energy conservation standards a lot of research is being done on turbocharger. The turbines in turbochargers are characterised mainly by A/R ratio. Varying A/R ratios can adversely affect the performance, fuel economy and emissions of a diesel engine due to effects of pressure boost, back pressure and exhaust gas recirculation. The current study deals with influence of A/R ratios of turbochargers on performance and emissions of a two-cylinder diesel engine. It is found from the experiments carried out that oxides of nitrogen emitted from the engine for all tested turbochargers showed the increasing trend from low to medium engine speeds and it is reverse trend from medium to higher speed range. The other engine emissions unburned hydrocarbon, carbon monoxide and smoke showed the inverse trend of oxides of nitrogen.